(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cancers are getting harder to treat because of poor editing efficiency within the tumors and the damage caused by conventional delivery methods. our study details a system that comprises of lipid nanoparticles (LNP) with a newly designed amino ionizable lipid for enhanced delivery of CRISPR-Cas9, in so doing breathing life to the notion of gene editing. The direct use of CRISPR-LNPs targeting PLK1 (injecting sgPLK1-cLNPs) into the brain of an advanced glioblastoma led to mmore than 65% gene editing within the body, this also led to a 45% decrease in the rate of tumor proliferation along with a 25% increase in overall survival. For metastatic tumors, the LNPs were additionally modified by several means and made for antibody-mediated targeting. EGFR targeting led to significant accumulation of the clip PLK1 containing LNPs to disseminated ovarian tumors implants, resulting in approximate 75%. This greatly inhibited the rate of tumor growth and increased longevity by approximately 70%. This study paves the way of utilizing nanoparticles containing CRISPR to easily and effortlessly target and edit cancerous cells. This work will profoundly alter the landscape of cancer therapy and gene editing techniques.